Food system innovations and digital technologies to foster productivity growth and rural transformation - Benfica, Rui; Chambers, Judith A.; Koo, Jawoo; Nin-Pratt, Alejandro; Falck-Zepeda, José B.; Stads, Gert-Jan; Arndt, Channing (Springer, 2023)
This chapter looks at food system innovations and digital technologies as important drivers of productivity growth and improved food and nutrition security. The analysis emphasizes a mix of research feasibility and technology-enabling policy factors necessary to realize pro-poor benefits. Given their transformative potential and the urgency of developing the enabling R&D and policy trajectories required for impact, we highlight genome editing bio-innovations, specifically CRISPR-Cas9, to address sustainable agricultural growth; and digital technologies, including remote sensing, connected sensors, artificial intelligence, digital advisory services, digital financial services, and e-commerce, to help guide the operations and decision-making of farmers, traders, and policymakers in agricultural value chains. The analysis points to the need to close critical gaps in R&D investments, capabilities, and enabling policies and regulations to accelerate the scaling and adoption of innovations. At the global level, the engagement of low- and middle-income countries (LMICs) with global players should be facilitated to strengthen intellectual property (IP) access and the management of innovations; and North–South, South–South, and triangular cooperation should be promoted to strengthen LMICs’ regulatory capabilities. At the national level, countries need to invest in science-based participatory approaches to identify and adapt technologies to local conditions; close regulatory gaps through evidence-based frameworks that enable the rapid development, deployment, and safe use of innovations; close institutional and human capacity gaps by addressing limitations in institutional capacities and coordination, while training a new generation of scientists with the skills needed to develop and deliver innovations; develop an understanding of political economy factors for a nuanced knowledge of actors’ agendas to better inform communications and address technology hesitancy; close digital infrastructure gaps in rural areas by promoting simultaneous investments in digital infrastructure and electrification, reducing data costs, and improving digital literacy; and develop sustainable business models for digital service providers to help them achieve profitability, interoperability, and scale to reach a sustainable critical mass, and thus facilitate the adoption of food system innovations.